2009
DOI: 10.1002/erv.937
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a sibling with anorexia nervosa: A qualitative study

Abstract: The findings from this qualitative study provide a window into the perceptions, feelings, and roles of siblings of women afflicted with AN. An intervention guided by the elicited themes may facilitate family functioning that is more adaptive for both siblings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(119 citation statements)
references
References 54 publications
10
107
0
2
Order By: Relevance
“…The marked impact on siblings and friends should also be highlighted. Dimitropoulos et al [17] have reported that siblings of anorexia nervosa patients actively involve themselves as mediators and protectors of their sick siblings and their parents, developing various adaptive strategies to deal with the challenges presented by the disease, and therefore can experience a lower HRQoL. In contrast, some authors have reported that siblings tend to isolate themselves and avoid the problem as much as possible [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The marked impact on siblings and friends should also be highlighted. Dimitropoulos et al [17] have reported that siblings of anorexia nervosa patients actively involve themselves as mediators and protectors of their sick siblings and their parents, developing various adaptive strategies to deal with the challenges presented by the disease, and therefore can experience a lower HRQoL. In contrast, some authors have reported that siblings tend to isolate themselves and avoid the problem as much as possible [20].…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have also tackled the question of QoL of caregivers of ED, but they also present some restraints. Specifically, they only recruited patients with one type of ED, such as anorexia nervosa [16,17] or bulimia nervosa [18], they only included parents as a type of caregiver [19] or only siblings [17,20], or do not measure specifically QoL but burden [21,22] or expressed emotion [16]. In the van Wijngaarden [22] study, they applied the Involvement Evaluation Questionnaire in 260 spouses and relatives of depressed patients, who reported being burdened by the caring process.…”
Section: Introductionmentioning
confidence: 99%
“…Siblings report worrying in silence and fear that the ill sibling might die,47 and they may feel uncomfortable to express feelings that would bring attention to themselves and adopt a role as an undemanding child7 or take on a role as a mediator between the ill sibling and the parents 9…”
Section: Introductionmentioning
confidence: 99%
“…The healthy siblings often have a great sense of responsibility and when the previous equal relationship between the siblings changes, the healthy sibling can assume a more parent-like role 1,57,9,11,12. The healthy siblings are often engaged in caregiving activities9,11 and have been suggested to have a beneficial influence on the ill sibling’s recovery 13. Despite this, few studies have explored the role of siblings and how the ill and the healthy siblings influence each other 4,8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation